Survival Strategies Of Indonesian Photojournalists In The Social Media Era: A Competency-Based Practices Study - Andry Prasetyo; Wahyu Novianto; Taufik Murtono (FAKULTAS DAKWAH UIN SALATIGA, 2025)
The digital disruption caused by social media has precipitated a crisis of relevance for professional photojournalists, blurring the lines between journalistic integrity and amateur content. While existing literature predominantly examines these structural shifts as external threats, there is limited research on the internal, agentic responses employed by practitioners to sustain their professional viability. This study examines the survival strategies used by elite Indonesian photojournalists (APFI award winners) in the era of social media. Employing a qualitative case study approach within an interpretivist framework, in-depth interviews were conducted with 13 award-winning members of Pewarta Foto Indonesia (PFI). The findings reveal that survival is not achieved by competing with the immediacy of social media, but through a